StMAPKK1 Enhances Thermotolerance in Potato (Solanum tuberosum L.) by Enhancing Antioxidant Defense and Photosynthetic Efficiency Under Heat Stress - Xi Zhu; Yasir Majeed; Kaitong Wang; Xiaoqin Duan; Nengkang Guan; Junfu Luo; Haifei Zheng; Huafen Zou; Hui Jin; Zhuo Chen; Yu Zhang (Plants)
The functional role of MAPKK genes in potato (Solanum tuberosum L.) under high-temperature stress remains unexplored, despite their critical importance in stress signaling and yield protection. We characterized StMAPKK1, a novel group D MAPKK localized to plasma membrane/cytoplasm. Quantitative real-time polymerase chain reaction (qRT-PCR) revealed cultivar-specific upregulation in potato (‘Atlantic’ and ‘Desiree’) leaves under heat stress (25 °C, 30 °C, and 35 °C). Transgenic lines overexpressing (OE) StMAPKK1 exhibited elevated antioxidant enzyme activity, including ascorbate peroxidase (APX), catalase (CAT), superoxide dismutase (SOD), and peroxidase (POD), mitigating oxidative damage. Increased proline and chlorophyll accumulation and reduced oxidative stress markers, hydrogen peroxide (H2O2) and malondialdehyde (MDA), indicate improved cellular redox homeostasis. The upregulation of key antioxidant and heat stress-responsive genes (StAPX, StCAT1/2, StPOD12/47, StFeSOD2/3, StMnSOD, StCuZnSOD1/2, StHSFA3 and StHSP20/70/90) strengthened the enzymatic defense system, enhanced thermotolerance, and improved photosynthetic efficiency, with significant improvements in net photosynthetic rate (Pn), transpiration rate (E), and stomatal conductance (Gs) under heat stress (35 °C) in StMAPKK1-OE plants. Superior growth and biomass (plant height, plant and its root fresh and dry weights, and tuber yield) accumulation, confirming the positive role of StMAPKK1 in thermotolerance. Conversely, RNA interference (RNAi)-mediated suppression of StMAPKK1 led to a reduction in enzymatic activity, proline content, and chlorophyll levels, exacerbating oxidative stress. Downregulation of antioxidant-related genes impaired ROS scavenging capacity and declines in photosynthetic efficiency, growth, and biomass, accompanied by elevated H2O2 and MDA accumulation, highlighting the essential role of StMAPKK1 in heat stress adaptation. These findings highlight StMAPKK1’s potential as a key genetic target for breeding heat-tolerant potato varieties, offering a foundation for improving crop resilience in warming climates.